2022
DOI: 10.1158/1078-0432.ccr-22-1922
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Infiltrating Lymphocyte Therapy in Melanoma: Facts to the Future

Abstract: Adoptive cell therapy with tumor-infiltrating lymphocytes (TILs) is gaining momentum and demonstrating durable responses in patients with advanced melanoma. Although increasingly considered as a treatment option for select patients with melanoma, TIL therapy is not yet approved by any regulatory agency. Pioneering studies with first-generation TIL therapy, undertaken before the advent of modern melanoma therapeutics, demonstrated clinical efficacy and remarkable long-term overall survival, reaching beyond 20 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 132 publications
0
12
0
Order By: Relevance
“…To enable an increased activity, one approach is to decrease the immunosuppressive effect in the TME through, for example, combining TIL therapy with checkpoint inhibitors. 67 Combining checkpoint inhibition with TIL therapy has been investigated in small studies, which showed feasibility and safety in 13 patients with metastatic melanoma, 68 and several trials are still ongoing (NCT02621021, NCT03374839, NCT03645928, NCT01701674). Furthermore, internal checkpoint alterations have yielded promising initial results as well, as presented by Palmer et al, 69 who used CRISPR/Cas9 to disrupt CISH, an internal regulator of T-cell effector function.…”
Section: Future Of Til Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…To enable an increased activity, one approach is to decrease the immunosuppressive effect in the TME through, for example, combining TIL therapy with checkpoint inhibitors. 67 Combining checkpoint inhibition with TIL therapy has been investigated in small studies, which showed feasibility and safety in 13 patients with metastatic melanoma, 68 and several trials are still ongoing (NCT02621021, NCT03374839, NCT03645928, NCT01701674). Furthermore, internal checkpoint alterations have yielded promising initial results as well, as presented by Palmer et al, 69 who used CRISPR/Cas9 to disrupt CISH, an internal regulator of T-cell effector function.…”
Section: Future Of Til Therapymentioning
confidence: 99%
“…Strategy 4: The last improvement strategy focuses on increasing T-cell function within the TME. To enable an increased activity, one approach is to decrease the immunosuppressive effect in the TME through, for example, combining TIL therapy with checkpoint inhibitors 67 . Combining checkpoint inhibition with TIL therapy has been investigated in small studies, which showed feasibility and safety in 13 patients with metastatic melanoma, 68 and several trials are still ongoing (NCT02621021, NCT03374839, NCT03645928, NCT01701674).…”
Section: Tumor-infiltrating Lymphocyte Therapymentioning
confidence: 99%
“…However, challenges remain, including the variability in response rates among patients and the logistical complexities involved in cell extraction and expansion. Moreover, the therapy’s side effects, such as cytokine release syndrome, necessitate careful patient monitoring [ 112 ]. Future research is directed towards enhancing the efficacy of TIL therapy through combination treatments, improving patient selection criteria, and understanding the genomic correlates of response to therapy [ 113 , 114 ].…”
Section: Molecular Therapeutic Strategiesmentioning
confidence: 99%
“…TIL can naturally target the tumor-specific antigen of the patient and infiltrate into the tumor tissue to kill tumor cells through direct contact or release of cytokines. This capability positions TIL as a promising solution to overcome the challenge of recognizing tumor antigens in the context of solid tumor therapy 7,8 . However, TIL therapy still faces challenges in the treatment of solid tumors due to various microenvironments and immune cell states of solid tumors.…”
Section: Introductionmentioning
confidence: 99%